VALIDATION OF SHEAR FAILURE ON BOLTED CONNECTION FOR NYATOH HARDWOOD - Xavier Langit, Ujan; Abdul Razak, Abdul Karim; Norazzlina, M. Sa'don; Siti Hanim, Sahari; Nur Liza, Rahim; Pierre, Quenneville (Taylor's University, 2023)
The lack of consideration of brittle failure by the Malaysian Timber Standard (MS544-5) in the design of bolted connections for local hardwood can be seen from the unacceptable under-design performance shown by the code. This makes the design output costly because of the increased use of steel materials due to either bigger bolt diameters or larger bolt quantities required. The current study was conducted to examine the effectiveness of the existing design equations for bolted connections in Nyatoh hardwood. This present study was to propose a set of optimised equations that can be used for the retrofit design of wall-diaphragm connections in unreinforced masonry buildings. The row shear failure observed in the tested bolted connections of Nyatoh hardwood was also reported. Ten different bolted connection configuration details in the manner of a steel-wood-steel arrangement were tested, which all had a single row bolted connection. By using the linear regression method in analysing the experimental data obtained, a calibration factor for optimising the Row Shear Model (RSM) equation was identified. From the comparisons made between the experimental results and the strength predictions given by both MS544-5 and RSM, it was found that the design strength calculated from MS544-5 was too conservative for predicting the bolted connection strength in Nyatoh hardwood, whereas the RSM predictions were acceptable and recommended.